Efforts to improve nutritional knowledge in adolescent girls through contemporary video-based education - Windi Indah Fajar Ningsih; Indah Purnama Sari; Feranita Utama (University of Merdeka Malang, 2024)
Adolescent girls belong to a vulnerable age group that experiences nutritional problems with various risks of health problems such as anemia, chronic energy deficiency, and overnutrition. Increasing the nutritional knowledge of adolescent girls can be an opportunity to improve their nutritional status throughout the initial 8000 days of life. This community service activity uses contemporary video media to expand the knowledge of adolescent girls related to nutrition. Community service is integrated with life-cycle nutrition courses. The target audience was 30 adolescent girls. This activity is located at SMA Negeri 4 Palembang for 1 month. The activity method was carried out by designing and making contemporary videos by 3rd-semester nutrition students, followed by distributing educational videos to participants. Feedback from participants as well as pre- and post-test results were used in the evaluation process. Results from community service projects show that 30% of targets have anemia based on Hb examination with the GC-Hb tool, and 30% of targets have malnutrition based on IMT/U assessment. The target's knowledge increased after providing education with contemporary videos (p<0.0001). After completing this community service project, it was concluded that the knowledge of adolescent girls increases by providing contemporary video-based nutrition education.